PELATIHAN MENINGKATKAN KETERAMPILAN BERBICARA DI DEPAN UMUM (PUBLIC SPEAKING) - Winstinindah Sandroto, Christine; Sozuaon Simbolon, Guru (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2024)
Public speaking skills improvement training was conducted as part of community service for STTELA students in Ampel Gading. This training was conducted based on a needs analysis to prepare students for service in the church or other Christian institutions after graduation. The resource person in this training was a full-time educator at the Faculty of Economics, Atma Jaya Catholic University of Indonesia, and a business practitioner who is also a part-time educator at STTELA. The training was conducted using a variety of methods, including icebreaking, explanatory materials, discussions, workshops/public speaking practices, and questions and answers from participants. The training went smoothly, and the participants were very enthusiastic. The workshop results showed that so many participants wanted to get the opportunity for a presentation. In the future, community service will continue to be carried out and can be sharpened with other soft skill topics.